Fibrinogen Vicenza and Genova II: Two New Cases of Congenital Dysfibrinogenemia with Isolated Defect of Fibrin Monomer Polymerization and Inhibitory Activity on Normal Coagulation - Rodeghiero, F; Castaman, G C; Peruffo, A Dal Belin; Dini, E; Galletti, A; Barone, E; Gastaldi, G (Thrombosis and Haemostasis, 1987)
Two new cases of congenital dysfibrinogenemia are presented in which defective fibrin monomer polymerization and inhibitory activity on normal coagulation were observed. They have been tentatively called fibrinogen Vicenza and Genova II. The first was discovered in a family with mild bleeding diathesis, the second in an asymptomatic family. In almost all reported cases of fibrinogens with defective fibrin monomer polymerization, additional functional or structural defects have been detected. In our cases, on the contrary, detailed investigations failed to show any other abnormality. Fibrinogen Genova II is apparently identical to fibrinogen Baltimore IV, whereas fibrinogen Vicenza is similar to fibrinogen Tloyes and Genovz I, but also exerts an evident inhibitory activity on normal coagulation and differs from fibrinogen Genova II and Baltimore IV showing a different kinetic pattern of fibrin monomer polymerization.
Keywords: Congenital coagulation defects; Dysfibrinogenemia; Fibrinogen Vicenza; Fibrinogen Genova II